Applicability of Western protocols in resource‐limited setting: Real‐world data of long‐term outcome of intensive treatment of adult acute myeloid leukaemia in Sri Lanka. Issue 3 (13th May 2021) - Hewamana, Saman; Kandabadage, Lakmali; Skandarajah, Thurairajah; Pieris, Natasha; Perera, Eranga; Harischandra, Mahesh; Wijewickrama, Ananda; Wickramarathna, Chandana; Somasundaram, Gnani; Srinivasan, Vadivelu; Somiah, Surjit; Jayawardena, Priyankara; et al.
Abstract: There are no published data on long‐term survival and applicability of treatment protocols from developed countries in acute myeloid leukaemia (AML) in Sri Lanka. Eighty‐seven AML patients were reviewed; there were 56 newly diagnosed patients between 18 and 65 years. Thirty‐one out of 33 who started treatment achieved complete remission after first cycle of treatment. The induction mortality was one of 33. Twelve out of 20 patients who completed treatment are alive at the time of analysis. The estimated 5‐year overall survival rate is 0.629. Strict infection control and treatment and superior clinical experience may have contributed towards better outcome.